Artisanal lime coatings and their influence on moisture transport during drying - Brito, V. (2013)
Lime coatings were originally used in historical buildings all across Europe and the rest of the globe, on lime plasters or directly on stone elements. Today, these coatings are increasingly used in conservation due to their unique aesthetic features but also for functional reasons. One of their main functional advantages is the ability to not hamper the drying of the substrate, which is very important because dampness is recurrent in historical buildings. The work presented here is aimed at improving the understanding of how and why lime coatings affect (or not) the drying of the porous building materials that usually constitute those substrates. For that, we have analysed experimentally the influence of one selected lime coating on the drying of five materials with architectural relevance: one lime mortar and four stones, among which the well-known Ançã limestone, Maastricht limestone and Bentheimer sandstone. The materials were characterized in relation to their capillary porosity and pore size distribution, and their drying kinetics when coated or uncoated was evaluated. The results showed that the lime coating not only does not hinder drying, but can even accelerate it. At high moisture contents, the drying rate can be increased up to around 50%. This is likely to happen because, due to the complexity of its pore structure, the coating generates a larger effective surface of evaporation. In this article we discuss the possible causes and implications of this phenomenon.